Strategi Tutor Dalam Meningkatkan Minat Belajar Pada Anak Usia Dini: - Hamidah, Ghalda; Putri, Yuli Yulianti; Sevic, Andre Okta; Nuraeni, Reni Siti; Yuliani, Lulu (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
This research reviews the Tutor's Strategy in Developing Learning Interest in Early Childhood. Tutors have an important role in developing interest in learning in early childhood. As we know, learning in early childhood is different from learning in general. Early childhood must be given more in-depth attention so that their interest in learning can increase. The purpose of this study is to find out and describe how the Tutor's strategy in Developing Learning Interest in Early Childhood at Kober Al Ittihad. This research uses descriptive qualitative research methods. Data collection techniques through observation, interviews, and documentation. While data analysis uses Miles and Huberman analysis techniques, namely data collection, data reduction, data presentation and verification. The results of this study are tutor strategies in developing interest in learning in early childhood at Kober Al Ittihad, namely by: telling stories, doing ice breaking before starting learning, playing games and using learning media that are as interesting as possible. The conclusion in this study is that the tutor's strategy in developing interest in learning in early childhood shows positive results. Through various innovative and interactive learning methods,through innovative and interactive learning, children's interest in learning will increase.